Meta-analysis of digital-based learning to improve learning outcomes - Ismiyati Ismiyati; Hengky Pramusinto; Mar'atus Sholikah; Nita Dwi Yulianti (Research and Social Study Institute, 2022)
The learning process in the 4.0 revolution era has changed from conventional systems to digital. It causes every component of education to use various features of digital technology as a learning medium, so this study aims to determine and analyze the effectiveness and influence of digital-based learning media on learning outcomes in economics subjects in senior and vocational high school. The meta-analysis by examining the results of research that are relevant to research variables from various research articles and theses is used in this study. Twenty-six studies examined digital-based cooperative learning media. The findings present that the effectiveness of digital-based learning media is effective in improving student learning outcomes. The quality of educators influences the effectiveness of using digital-based learning media in learning materials according to the tools or media used so that students' enthusiasm in participating in learning increases.